2012
DOI: 10.1007/s11102-012-0453-1
|View full text |Cite
|
Sign up to set email alerts
|

Post-operative diabetes insipidus after endoscopic transsphenoidal surgery

Abstract: Diabetes insipidus (DI) after endoscopic transsphenoidal surgery (ETSS) can lead to increased morbidity, longer hospital stays, and increased medication requirements. Predicting which patients are at high risk for developing DI can help direct services to ensure adequate care and follow-up. The objective of this study was to review our institution's experience with ETSS and determine which clinical/laboratory variables are associated with DI in this patient population. The authors wanted to see if there was an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
72
3
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(82 citation statements)
references
References 25 publications
2
72
3
5
Order By: Relevance
“…Most irregularities are transient, presenting within 1 to 14 days after surgery and typically resolving during this same time period. Diagnosis of such electrolyte imbalances requires a high degree of suspicion as well as close clinical and laboratory follow‐up, to prevent potentially catastrophic complications …”
Section: Intradural Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most irregularities are transient, presenting within 1 to 14 days after surgery and typically resolving during this same time period. Diagnosis of such electrolyte imbalances requires a high degree of suspicion as well as close clinical and laboratory follow‐up, to prevent potentially catastrophic complications …”
Section: Intradural Tumorsmentioning
confidence: 99%
“…Transient DI typically presents within 24 to 48 hours after surgery with polyuria and generally resolves around postoperative days 3 to 5. Several large endoscopic series report the incidence of transient DI ranging from 4.6% to 8.7% . Furthermore, recent studies comparing endoscopic and microscopic transsphenoidal adenoma resection indicate a decreased incidence of DI in patients undergoing endoscopic resection of pituitary adenomas (4.6% vs 38.5%) .…”
Section: Intradural Tumorsmentioning
confidence: 99%
“…The suggested risk factors that predispose to postoperative complications after pituitary surgery are tumor volume and histopathology, advanced age, body mass index, repeat operation, and previous radiotherapy [10,32,33]. In this study, the only identified risk factor for the onset of any postoperative complication was larger tumor size, specifically the width of the tumor.…”
Section: Risk Factorsmentioning
confidence: 66%
“…CDI belong to the polyuric-polydipsic syndrome, a group of disorders characterized by hypotonic polyuria mostly associated with compensatory polydipsia. CDI acquired forms are often surgical complication of pituitary surgery (18.3-31%) responsible for electrolyte disturbances and elevated morbidity in neurosurgical patients [3]; endoscopic minimally invasive technique has been associated with a lower rate of post-surgical CDI [4][5][6][7][8]. A transient AVP deficiency, due to dysfunction of the magnocellular hypothalamic neurons, is the most common pattern of presentation of CDI following surgical manipulation.…”
Section: Introductionmentioning
confidence: 99%
“…Although several risk factors have been identified for developing postoperative CDI (i.e., craniopharyngioma, Rathke's cleft cyst, maximal tumour diameter, intraoperative cerebrospinal fluid leak, visual abnormalities, young age, male sex), this disorder lacks widely agreed diagnostic criteria [3][4][5][6][7][8][9][10]. Because AVP plays a key role in the hydro-electrolytic regulation and in the pathophysiology of CDI, direct measurement of this neurohormone in the postoperative could contribute decisively to the early diagnosis.…”
Section: Introductionmentioning
confidence: 99%